Influential Article Review- How does the State Function in a Digital World? - Herrera, Marcia; Patton, Mable; Bell, Stanley (Journal of Leadership, Accountability and Ethics, 2019)
This paper examines government and digitalization. We present insights from a highly influential paper. Here are the highlights from this paper: Past and potential contributions of the state to innovation and the creation of the digital economy need to be understood now, more than ever. The state is under attack, and its role in innovation and technological transformation is being increasingly challenged and dismantled in many countries. This article takes an alternative view of the state role in the digital age, one that is supported by historical evidence. The article examines the increasing demand for an entrepreneurial state and draws on lessons from pioneering countries. It shows the variety of roles and strategies that the state can play in creating the digital economy. These roles include nurturing a national digital transformation ecosystem and building an innovative and inclusive digital economy. These roles call for new state capabilities to fit with the demands of the digital age. This is a call for strategic learning and partnership, not for dirigisme and protectionism. The paper proposes an agenda for learning to master digital transformation and suggests that the appropriate role of the state must evolve in sync with a learning economy and society. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.